Increasing Nationalism of Primary School Students Through Learning Dongkrek Art By Using Powepoint-Based Comics - Muhammad Hanif (Syntax Literate, 2022)
This research aims to increase the value of nationalism for elementary school students. The increase in nationalism can be achieved by learning art, especially the art of dongkrek which is one of the original cultural heritages of Madiun Regency. This research is a class action research carried out in class 5 at the State Elementary School 02 in Sirapan Village Regency. Most students are happy with learning dongkrek art using powepoint-based comics. The level of mastery learning classically reaches 94%.